Transdisciplinary method for water pollution and human health research - Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2010)
This paper discusses how to go about designing an interdisciplinary or transdisciplinary research project or programme, with ZEF's research initiative on 'water pollution and human health' in India as the background of the presentation. A summary is given of Pohl and Hirsch Hadorn's (2007) main arguments regarding 'design principles' for inter- and transdisciplinary research, and the basic tools they have developed for this are discussed in the context of ZEF's 'water pollution and human health' research initiative.
Keywords: 330; transdisciplinarity; human health; water pollution; method